2021
DOI: 10.1021/acscatal.1c01698
|View full text |Cite
|
Sign up to set email alerts
|

FUT8-Directed Core Fucosylation of N-glycans Is Regulated by the Glycan Structure and Protein Environment

Abstract: FUT8 is an essential α-1,6-fucosyltransferase that fucosylates the innermost GlcNAc of N-glycans, a process called core fucosylation. In vitro , FUT8 exhibits substrate preference for the biantennary complex N-glycan oligosaccharide (G0), but the role of the underlying protein/peptide to which N-glycans are attached remains unclear. Here, we explored the FUT8 enzyme with a series of N-glycan oligosaccharides, N-glycopeptides, and an Asn-linked oligosaccharide. We found that the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…21 Normally during SGP purification the monoantennary glycopeptide is removed by size exclusion chromatography 22 or digested enzymatically to afford a homogenous albeit degalactosylated glycan. 23,24 Despite previous evidence for the presence of the monosialylated asymmetric glycan in egg yolk, recent publications identify it as a mixture. 25 Having an alternative source of asymmetric glycans would be of interest since they are difficult to synthesize and there is growing awareness of the biological implications of N-glycan asymmetry such as the complement-dependent cytotoxicity of monoclonal antibodies, 26 and influenza haemagglutinin binding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Normally during SGP purification the monoantennary glycopeptide is removed by size exclusion chromatography 22 or digested enzymatically to afford a homogenous albeit degalactosylated glycan. 23,24 Despite previous evidence for the presence of the monosialylated asymmetric glycan in egg yolk, recent publications identify it as a mixture. 25 Having an alternative source of asymmetric glycans would be of interest since they are difficult to synthesize and there is growing awareness of the biological implications of N-glycan asymmetry such as the complement-dependent cytotoxicity of monoclonal antibodies, 26 and influenza haemagglutinin binding.…”
Section: Introductionmentioning
confidence: 99%
“…21 Normally during SGP purification the monoantennary glycopeptide is removed by size exclusion chromatography 22 or digested enzymatically to afford a homogenous albeit de-galactosylated glycan. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the case of GalNAc-T2, the active conformation of GalNAc-T2, characterized by the shifting of a flexible loop from an open to a closed conformation, was completely achieved in the presence of UDP-GalNAc and less in the presence of UDP 20 . We also found that the GT-B fold FUT8 showed similar properties to the other two GTs, though FUT8 bound better to an N-glycan in the presence of GDP, and the nucleotide was not essential for binding to the N-glycan 37 , 38 . In addition, NleB/SseK and FUT8 also contained flexible loops that were ordered in the presence of the nucleotide as we found for GalNAc-T2, implying that the active site adopted an active conformation once that these flexible loops bound to the sugar nucleotide 20 , 35 , 36 , 38 .…”
Section: Resultsmentioning
confidence: 59%
“…Core fucosylation is the attachment of an ⍺1,6-linked fucose to the GlcNAc that is directly attached to the asparagine at the core of N-linked glycans, a reaction which is catalyzed by the fucosyltransferase FUT8. This reaction is generally specific to complex N-glycans ( 44 ), and thus, we generated GlcNAc 2 Man 3 GlcNAc 2 glycans on our collection of reporter proteins by reacting with an excess of MGAT1, MAN2A1, and MGAT2 in the presence of the UDP-GlcNAc sugar donor. We then examined the rates of modification of the respective glycans with FUT8 ( Fig.…”
Section: Resultsmentioning
confidence: 99%